Assessing Default Risks for Chinese Firms : A Lost Cause? - Law, Daniel (IMF Working Papers; Working Paper ;, 2015)
Assessing default risks for Chinese firms is hard. Standard measures of risk using market indicators may be unreliable because of implicit guarantees, the large role played by less-informed investors, and other market imperfections. We test this assertion by estimating stand-alone 1-year default probabilities for non-financial firms in China using an equity-based structural model and debt costs. We find evidence that the equity measure of default risk is sensitive to a firm's balance sheet health, profitability, and ownership; specifically, default probabilities are higher for weaker, less profitable, and state-owned firms. In contrast, measures based on the cost of debt seem largely detached from fundamentals and instead determined by implicit guarantees. We conclude that for individual firms, equity-based measures, while far from perfect, provide a better measure of stand-alone default risks than borrowing costs.